2017
DOI: 10.1080/13510002.2017.1372072
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of antioxidant status and lipid peroxidation in elderly patients with hypertension

Abstract: Hypertension in elderly patients is accompanied by changes in biomarkers of antioxidant status and lipid peroxidation status, which significantly differ from those observed in healthy ageing subjects. Our study also suggests that the relationship of gender and changes in redox balance with regard to hypertension should be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
3
16
0
2
Order By: Relevance
“…Nonetheless, after reviewing the treatment used for DM patients, we found that most of them include anti-oxidants 17 . Also, it is known that certain drugs used for the treatment of HA interact with the antioxidant enzymes like superoxide dismutase (SOD) and catalases (CAT); patients with no HA treatment have a reduced activity of these enzymes, while patients receiving treatment for hypertension show an increased activity of both 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, after reviewing the treatment used for DM patients, we found that most of them include anti-oxidants 17 . Also, it is known that certain drugs used for the treatment of HA interact with the antioxidant enzymes like superoxide dismutase (SOD) and catalases (CAT); patients with no HA treatment have a reduced activity of these enzymes, while patients receiving treatment for hypertension show an increased activity of both 13 .…”
Section: Discussionmentioning
confidence: 99%
“…An increase in ROS production and lipid peroxidation has been reported in patients with DM, where chronic damage by OS is associated to occurrence and complications of the disease 12 . Moreover, in patients with HT it is known that OS alters the function of the endothelium and has a direct effect on the vascular contraction, due to the reduction of NO 13 . The increase in OS generates other alterations in the regulatory system that affect hypertension, including the positive regulation of the renin-angiotensin-aldosterone system, the activation of the sympathetic nervous system, the disturbances of the cellular signalling of the G-protein, inflammation, and alteration of T-cells function 13 .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that hypertension is associated with an increased degree of lipid peroxidation [20], so we measured the levels of one of the products of lipid peroxidation, malondialdehyde (MDA), in rat serum. The levels of MDA products in the serum were used as an indicator for the degree of lipid peroxidation ( Figure 2D).…”
Section: Single Oral Dose Of P-spi Improves Serum Parameters Associatmentioning
confidence: 99%
“…Îñîáëèâó óâàãó ïðèä³ëÿºòüñÿ âèâ÷åííþ åíäîòåë³éíî¿ äèñôóíêö³¿ ïðè àðòåð³éí³é ã³ïåðòåí糿. Ñåðåä âàaeëèâèõ ÷èííèê³â ðåãó-ëÿö³¿ àðòåð³éíîãî òèñêó âèä³ëÿþòü L-àðã³í³í, îêñèä àçîòó [19 ], ñ³ðêîâîäåíü [21].…”
Section: âñòóïunclassified
“…Òàê, â³äì³÷àâñÿ ñèëüíèé êîðåëÿòèâíèé âçàºìîçâ'ÿçîê ì³ae L-àðã³í³íîì òà NO, à òàêîae íå´àòèâíèé çâ'ÿçîê ñåðåäíüî¿ ñèëè ì³ae L-àð-ã³í³íîì òà í³òðàòàìè ÿê äî, òàê ³ ï³ñëÿ ô³çè÷íîãî íàâàíòàaeåííÿ. ³äîìî, ùî L-àðã³í³í âèñòóïຠñóáñòðàòîì äëÿ ïðîäóêö³¿ NO, à í³òðàòè º ïðîäóêòîì ìåòàáîë³çìó í³òðî´åí îêñèäó [19].…”
Section: ðåçóëüòàòè é îáãîâîðåííÿunclassified